1987
DOI: 10.1515/znc-1987-11-1230
|View full text |Cite
|
Sign up to set email alerts
|

MHC-Antigens: Constituents of the Envelopes of Human and Simian Immunodeficiency

Abstract: Immunoelectron microscopy was applied to study the antigenic make-up of human and simian immunodeficiency viruses (HIV, SIV) grown in cells expressing either MHC class I (Molt-3) or MHC class I and II (H9) antigens. A variety of antibodies directed against the surface glycopro­ tein gpl20 of HIV and against MHC class I and II antigens were employed. Consistent with earlier observations on the loss of HIV envelope components, gp120 was only weakly demonstra­ ble on the mature virion. MHC class I determinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

1993
1993
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 0 publications
0
26
0
4
Order By: Relevance
“…Therefore, we propose a different mechanism for HIV-1 infection of CD4 cells, occurring independently of HIV-1 envelope proteins. It has been reported that cellular membrane proteins are incorporated into the viral lipid envelope during budding (12). It is possible that these cellular membrane proteins in the viral envelope interact with appropriate receptors on the surface of some target CD4 Ϫ cells, thus facilitating entry of the virus into the target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we propose a different mechanism for HIV-1 infection of CD4 cells, occurring independently of HIV-1 envelope proteins. It has been reported that cellular membrane proteins are incorporated into the viral lipid envelope during budding (12). It is possible that these cellular membrane proteins in the viral envelope interact with appropriate receptors on the surface of some target CD4 Ϫ cells, thus facilitating entry of the virus into the target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Magnification: x 120,000. (e, f) Immuno EM localization of HLA class I (beta 2 microglobulin) and of class II (HLA DR), respectively, on budding and mature HTV-1 (from Gelderblom et al, 1987b). Magnification.…”
Section: The Assembly Of the Viral Envelopementioning
confidence: 99%
“…Constituents of the viral envelope The lipids of the viral envelope are derived from the plasma membrane of the virus-producing cell during budding (Aloia et al, 1993). Besides SU and TM, a number of cellular proteins have been demonstrated to be present on HIV and SIV by immuno EM and other immunological techniques (Gelderblom et al, 1987b;Henderson et al, 1987;Hoxie et al, 1987;Meerloo et al, 1993). For example, HLA class I or HLA DR (class IT) proteins are tightly inserted during budding into the viral envelope (Fig.…”
Section: Structure and Composition Of The Mature Virionmentioning
confidence: 99%
“…Cross sections of cells which have been embedded, stained, and visualized with TEM show the presence of virions near and at cell surfaces in the processes of maturation and budding (10,21,23,68). Those images are revealing and quite remarkable, but they do have certain limitations.…”
mentioning
confidence: 99%